Teasing out History: Rushdie’s Midnight’s Children towards Mock Heroism - Adhikari, Tara Prasad (The Harvest, 2023)
This paper claims that Rushdie develops his protagonist Saleem as an unreliable anti-hero. In doing so, the novel borrows tools and techniques of Mock Heroism. The Restoration and Augustan authors John Dryden and Alexander Pope are chiefly responsible for the mock-heroic genre. A mock-heroic book parodies the heroic style in literature in a sarcastic fashion, mimicking the actions or manner of a hero, often comically in nonheroic circumstances. Saleem claims to be the new India’s voice, taking on significant political responsibility and “evoking” these heroic deeds. He is, however, powerless, nd his magical ability to spy on people is dependent on a disproportionately large nose. His reliance on his cucumber nose to sense the true history is really hilarious. In this sense, Saleem is undoubtedly an absurd hero because his attempt to recapture what has been already lost is an absurdist attempt. Saleem is well aware that his historical account of India will be incomplete anyway. Despite this, he does not hesitate to boast that he is the truest of the historians and his version of India is much better.